Knowledge, attitudes and perceptions towards date rape among Midlands State University students - Chiwara, Tafadzwa (Midlands State University, 2017)
The research study examined the level of knowledge, attitudes and perceptions towards date rape among university students. Hundred and fifty (150) university students participated and the sample population was drawn from the Midlands State University using convenience sampling. The research study adopted a quantitative approach. A questionnaire used to assess the knowledge, attitudes and perceptions towards date rape was developed from the College Date Rape Attitude and Behaviour Survey (CDRABS), created by Larnier & Elliot (1997). The results from the findings indicate that most university students have knowledge of date rape, however because of cultural believes and rape myths that determine the way individuals view and perceive date rape, it is underrecognised and is not regarded as something unacceptable. Midlands State University students portrayed neutral attitudes and perceptions towards date rape. When compared to Western countries the kind of attitudes and perceptions are significantly different. This may be related with the fact that there are differences in cultural beliefs between the Western and African cultures. Date rape is under recognized in Zimbabwe. Most factors influenced the level of knowledge, kind of attitudes and perceptions that college students have towards date rape. However the researcher observed that the significance for perceptions and level is 0.700 and significance for knowledge and marital status was 0.684, indicating that there was no significant differences between and within groups of students in perceptual experiences and understanding of date rape. The research study recommends further research to assess the prevalence of date rape among university students.